Donor‐derived tuberculosis (TB): isoniazid‐resistant TB transmitted from a lung transplant donor with inadequately treated latent infection. Issue 5 (7th September 2016) - Jensen, T.O.; Darley, D.R.; Goeman, E.E.; Shaw, K.; Marriott, D.J.; Glanville, A.R.
Abstract: Donor‐derived tuberculosis (TB) is an increasingly recognized complication of solid organ transplantation. We report a case of isoniazid‐resistant pulmonary TB in a lung transplant recipient. The patient acquired the infection from the lung donor who was previously empirically treated with isoniazid for latent TB. The case highlights the caveat that, while adequate treatment of latent TB with isoniazid is presumed, meticulous screening of donors is required.